Networked Learning and Knowledge Management: A Systemic Challenge for Universities - Baumeister, Hans-Peter (Proceedings of the International Conference on Networked Learning, 2004)
Networked/Online or e-learning is a multi-dimensional phenomenon which needs to be understood not only in intrinsic terms but as it relates to the societal environment within which it is applied. There are various ways of defining the term but, for the purposes of this paper, Rosenberg's three-fold categorization has been adopted: online Learning is networked, which makes it capable of instant updating, storage/retrieval; distribution and sharing of instruction or information, can also follow instantly. It is delivered to the end-user via a computer using standard Internet technology. It can be arranged as a stand-alone or hybrid solution (embedded in a traditional context). It focuses on the broadest view of learning – learning solutions that go beyond the traditional paradigms of training (Rosenberg, 2001). Hence it is difficult to separate online learning (which applies more the technical background as the core of the definition) from networked learning (which is implicitly covered by the above definition) or from technology enhanced learning a term now used by the European Commission (which starts from the assumption of "blended learning" approaches). Bearing in mind Rosenberg’s definition, for the purposes of this paper, the term networked learning is also used as a synonym for online and/or e-learning.